Online Customer Review, Online Customer Rating, and Payment Guarantee Influence on Purchase Intention - Ananda, Putu Divira Vidya; Yasa, Ni Nyoman Kerti; Ekawati, Ni Wayan; Warmika, I Gde Ketut (Jurnal Ekonomi dan Bisnis Jagaditha, 2023)
The purpose of this study was to analyze the effect of online customer reviews, online customer ratings, and payment guarantees on the purchase intention of e-commerce Shopee consumers in Denpasar. This study used a quantitative approach which was carried out on e-commerce Shopee consumers in Denpasar by using a questionnaire on 130 respondents. The data analysis technique used is multiple linear regression. The results of the study show that online customer reviews have a positive and significant effect on the purchase intention of e-commerce Shopee consumers in Denpasar. The online customer rating has a positive and significant effect on the purchase intention of e-commerce Shopee consumers in Denpasar. The payment guarantee has a positive and significant effect on the purchase intention of e-commerce Shopee consumers in Denpasar.